Ethical Dilemmas in Academic Staff Promotion in Nigerian Universities – Developing an Equity-Based Evaluation Model - Asabor, Mary Bivwiere; Alordiah, Caroline (NIU Journal of Social Sciences; Vol 11 No 2 (2025): NIU Journal of Social Sciences, Vol. 11 No. 2, June 2025, 2025)
This paper investigates the ethical challenges present in the promotion processes of academic staff at Nigerian universities, suggesting an equity-centred evaluation model as a viable solution. The report conducts a critical analysis of existing frameworks, revealing systemic weaknesses such as gender imbalances, ethnic favouritism, inconsistent evaluation methods, and opaque decision-making that compromise meritocracy and institutional legitimacy. The suggested paradigm presents four fundamental principles: openness, meritocracy, inclusion, and accountability, implemented via defined evaluation measures, bias mitigation strategies, and independent monitoring systems. A comparative comparison with global best practices yields proposals for policy reform, encompassing the standardisation of promotion criteria, compulsory bias training for evaluators, and the creation of grievance resolution channels. The research contends that the adoption of equitable promotion methods will bolster institutional reputation, promote teacher retention, and prepare Nigerian universities for global competition. The findings underscore the pressing necessity for cooperative efforts among university administrators, regulatory agencies, and faculty associations to convert promotion regimes into authentic meritocracies. Keywords : Academic promotions, equity-based evaluation, Nigerian universities, meritocracy, ethical dilemmas, faculty advancement, higher education reform, promotion bias, institutional equity, NUC guidelines